2022
DOI: 10.1186/s12979-022-00295-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term zinc supplementation of zinc-deficient seniors counteracts CREMα - mediated IL-2 suppression

Abstract: Background Aging is accompanied by a dramatic decline in the interleukin (IL)-2 production capacity of human immune cells, thus making seniors more susceptible to a variety of age-related diseases. A common cause of impaired cytokine production in advanced age is a deficiency of the essential micronutrient zinc. Nevertheless, the molecular mechanisms underlying a zinc deficiency-induced decrease in IL-2 production have not yet been satisfactorily elucidated. Recent animal and in vitro data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…It was previously shown that IFN-γ and IL-2 expression are regulated by intracellular zinc [ 9 , 11 , 18 , 22 ]; thus, we next examined the distribution of intracellular-free zinc in PPI-treated PBMC. The lysosome-free zinc concentration was determined by FluoZin-3 AM, and the cytoplasm-free zinc concentration was determined by Zinpyr-1 staining.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously shown that IFN-γ and IL-2 expression are regulated by intracellular zinc [ 9 , 11 , 18 , 22 ]; thus, we next examined the distribution of intracellular-free zinc in PPI-treated PBMC. The lysosome-free zinc concentration was determined by FluoZin-3 AM, and the cytoplasm-free zinc concentration was determined by Zinpyr-1 staining.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the reduced expression of IL-2 in the PPI-treated PBMC, we examined CREMα, which has been shown to inhibit IL-2 transcription in zinc deficiency [ 11 , 22 ]. The human CREM gene consists of 20 exons [ 26 , 27 ], and alternative splicing results in many different isoforms that have different, even opposite, effects on target gene expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Zn, its role in the optimal function of the immune responses appears particularly crucial, as old mice with reduced zinc levels reported an increased proinflammatory cytokines profile, such as MCP1 and IL6 in the serum, also showed increased Th1/Th17/inflammatory cytokines (IFNγ, IL17, TNFα, respectively), and decreased naïve CD4 T-cells in the mesenteric lymph nodes (MLN) [ 92 ]. The ability to enforce immunity in the elderly and to delay the immunosenescence mechanism is a leading role of these trace elements, usually in the form of metal cofactors [ 93 , 94 , 95 , 96 ].…”
Section: Trace Elements and Micronutrientsmentioning
confidence: 99%
“…Similar results were uncovered for healthy men having a restricted zinc diet for 10 weeks, resulting in reduced IL-2R production [ 265 ]. In parallel, studies uncovered the transcription factor cAMP-responsive element modulator alpha (CREMα) to be upregulated due to zinc deficiency, leading to dampened IL-2 production [ 266 , 267 ].…”
Section: Zinc and The Inflamed Immune Systemmentioning
confidence: 99%